Sustained efficacy of the monoclonal anti-interleukin-1 beta antibody canakinumab in a 9-month trial in Schnitzler's syndrome. Issue 10 (19th October 2012) - de Koning, Heleen D; Schalkwijk, Joost; van der Ven-Jongekrijg, Johanna; Stoffels, Monique; van der Meer, Jos W M; Simon, Anna
Abstract : Objectives: Schnitzler's syndrome is a chronic disabling autoinflammatory disorder, characterised by chronic urticaria, paraproteinemia and systemic inflammation. The interleukin (IL) 1 receptor antagonist anakinra is a very effective treatment, but requires daily injection and blocks both IL-1α and IL-1β. Canakinumab is a selective human monoclonal anti-IL-1β antibody with a long half-life. We investigated the long-term efficacy and safety of canakinumab in Schnitzler's syndrome. Methods: In an open-label, single-treatment arm trial, eight patients with Schnitzler's syndrome received monthly injections with 150 mg canakinumab subcutaneously for 6 months, followed by a 3-month observation period. Primary outcome was complete or clinical remission at day 14. Secondary outcome measures included inflammatory markers, quality of life, time to relapse, safety and tolerability. Results: After stopping anakinra, patients developed moderate to severe clinical symptoms. Canakinumab induced complete or clinical remission at day 14 in all eight patients. Median C-reactive protein concentrations decreased from 169 mg/l at baseline to less than 10 mg/l on day 14 and remained low or undetectable. One patient discontinued participation on day 39 because of return of symptoms while all others remained in complete or clinical remission during the 6-month treatment period. Relapse after last canakinumab dose occurred within 3 months in four patients. For two patients, remission continued several months post-study. Five patients reported at least one adverse event, predominantly mild upper respiratory tract infections. One patient died in a traffic accident. Conclusions: In this 9-month study, monthly 150 mg canakinumab injection was an effective and well-tolerated treatment for Schnitzler's syndrome. Our data demonstrate that IL-1β plays a pivotal role in this disease. ClinicalTrials.gov: NCT01276522.